The efficacy and safety of acetaminophen use following liver resection: a systematic review. Issue 1 (January 2022) - Murphy, Victoria; Koea, Jonathan; Srinivasa, Sanket
Abstract: Purpose: Acetaminophen is commonly used for post-operative analgesia following liver resection. It is metabolised by the liver and appropriate administration and dosage is in question in in patients undergoing hepatectomy. A systematic review was conducted to investigate safety and efficacy of acetaminophen use. Methods: MEDLINE, EMBASE, PubMed, Web of Science, and Google Scholar were searched for instances of toxicity, liver dysfunction, and analgesic efficacy in patients undergoing hepatectomy. Results: Two randomised controlled trials and four prospective observational studies were included. The studies were of moderate quality. Four studies investigated post-operative levels of acetaminophen and its urinary metabolites, finding no evidence of toxicity. One study noted that glutathione levels decreased but not to clinically deficient levels. Administration of acetaminophen plus morphine versus morphine alone did not increase adverse events and a morphine sparing effect of acetaminophen was demonstrated in two studies. Conclusion: Use of acetaminophen for adult patients undergoing liver resection surgery as post-operative analgesia at a standard dosage is safe for baseline analgesia. All studies analysed support that toxicity is not reached; and that acetaminophen provides a morphine sparing effect without adverse effects. Acetaminophen dose reduction should be considered in patients where extra risk factors for hepatotoxicity are present.